Overexpression of Anti-müllerian Hormone Gene in vivo Affects Gonad Sex Differentiation in Undifferentiated Orange-Spotted Groupers (Epinephelus coioides) - Han, Yulong; Zhao, Mi; Wang, Le; Yu, Zeshu; Wang, Jing; Yu, Qi; Xiao, Ling; Lu, Mingwei; Li, Shuisheng; Zhang, Yong; Lin, Haoran (Frontiers in Endocrinology, 2019)
Introduction Sex differentiation in teleost fishes occurs in response to sex-determination signals, which induce the gonad to develop as either an ovary or testis. However, sex differentiation mechanisms in fishes are diverse, and information on gonad differentiation in sex changing fishes remains limited. The orange-spotted grouper (Epinephelus coioides) is a protogynous hermaphroditic fish that provides an ideal model for investigating gonad differentiation in vertebrates. In this study, we investigated the effect of overexpressing anti-Müllerian hormone (Amh) on gonad development in juvenile orange-spotted groupers. Transcriptome data showed that expression levels of amh and amhrII in gonads were increased during sex differentiation. Furthermore, expression levels of female-related genes and serum 17β-estradiol levels were decreased, while expression of male-related genes and serum 11-ketotestosterone levels were increased in fish fed amh-plasmid. Overexpression of Amh was also associated with spermatogonia proliferation and a tendency towards male gonad development. In summary, these results illustrated that Amh overexpression by amh-plasmid feeding induced male gonad development in undifferentiated groupers.